Development of Online Learning Media Using Geogebra and LaTeX on Derivative Material - Arifin, M Zainul; Danaryanti, Agni; Suryaningsih, Yuni (Indonesian Journal of Science and Mathematics Education, 2023)
Learning media in online learning is needed to understand mathematical concepts such as derivative material. Students need help connecting the derivative material with other materials, such as tangent equations. Technology-based learning media can be an alternative to help students improve their understanding of derivative concepts, one of which uses GeoGebra and LaTeX. The final product expected from this research is online learning media in the form of the GeoGebra web that students can access easily, which is in the valid category. This research is development research with a 4D development model. Due to the limitations of researchers, only three stages were carried out, namely, Define, Design, and Develop. The data collected in this study were obtained through validation sheets. Three experts carried out validation. The results of the validity test of the learning media developed belonged to the valid category with a score of 3,79. It can be concluded that online learning media is appropriate for use in classroom learning.